Shades of Che: reconstructing the Multiple Identities of Ernesto Che Guevara in I. Lavretsky's 'Ernesto Che Guevara' - Javangwe, Tasiyana D. (2016)
Ernesto Che Guevara is a highly celebrated and vilified figure in Latin American and world history. Both those who vilify and celebrate him tend to focus on his ideological, leadership and military identities. Given his life trajectory, this focus is both unavoidable and essential. This paper intends to go further and explore Che's more marginalised identities. These include his childhood identities, hereditary, embodied selves, prisoner, victim and messianic identities. It is hoped that this will contribute to the construction of a more holistic memory of one of Latin America's most enigmatic figures. The paper explores these identities while at the same time interrogating the extent to which the biographical narrative can reconstruct and adapt itself to new readings and meanings of such a controversial life as that of Che.